Gaussian solitary waves to Boussinesq equation with dual dispersion and logarithmic nonlinearity - Biswas, Anjan; Ekici, Mehmet; Sonmezoglu, Abdullah (Nonlinear Analysis: Modelling and Control, 2018)
This paper discusses shallow water waves that is modeled with Boussinesq equation that comes with dual dispersion and logarithmic nonlinearity. The extended trial function scheme retrieves exact Gaussian solitary wave solutions to the model.